Splošna in anorganska kemija: Navodila za laboratorijske vaje študijskega programa Farmacija - Slemnik, Mojca; Stergar, Janja; Ban, Irena (University of Maribor Press, 2026)
General and Inorganic Chemistry: Instructions for Laboratory Exercises in the Pharmacy Study Program. This book is a collection of instructions for conducting practical experiments in general and inorganic chemistry for pharmacy students. Students are introduced to the basics of laboratory work: they become familiar with laboratory equipment, master basic laboratory techniques and their application in setting up apparatus for chemical experiments, link computational tasks to experiments, learn how to write reports, and become acquainted with safety procedures in the chemistry laboratory.